Motives to Have Sex: Measurement and Correlates With Sociodemographic, Sexual Life, and Psychosexual Characteristics - Barrada, Juan Ramón; Castro, Ángel; Fernández-del-Río, Elena; Ramos-Villagrasa, Pedro J. (Frontiers in Psychology, 2021)
Knowledge of diverse sexual motivations can have profound implications for our comprehension of the causes, correlations, and consequences of sexual behavior. This study had two objectives: on the one hand, to determine the different motives why young Spanish university students have sex and their relationship with different sociodemographic and psychosexual variables and sexual behavior; on the other hand, to review and improve the psychometric properties of the Sexual Motivations Scale and validate it in Spanish. Participants were 805 university students of both sexes (78% women, 74% heterosexuals), aged between 18 and 26 years (Mage = 20.88), who completed a battery of online questionnaires. Significant associations were found between young people's sexual motives, especially the motives of coping, peer pressure, and enhancement, the sociodemographic variables (sex, age sexual orientation, relational status), sexual behavior (age of initiation), and psychosexual variables (sociosexuality, self-esteem as a sexual partner, satisfaction with sex life). Also, a new structure of the Sexual Motivations Scale was proposed, with the elimination of the factor of Self-Affirmation. The discussion highlights the relevance of the results obtained due to their implications in the promotion of sexual health, in addition to achieving the first instrument validated in Spanish for the evaluation of sexual motivations.